Pharmacogenetic interaction between dexamethasone and Cd36-deficient segment of spontaneously hypertensive rat chromosome 4 affects triacylglycerol and cholesterol distribution into lipoprotein fractions - Krupková, Michaela; Sedová, Lucie; Liska, Frantisek; Krenová, Drahomíra; Kren, Vladimír; Seda, Ondrej (Lipids in health and disease, 2010)
Dexamethasone (DEX) is known to induce diabetes and dyslipidemia. We have compared fasting triacylglycerol and cholesterol concentrations across 20 lipoprotein fractions and glucose tolerance in control (standard diet) and DEX-treated 7-month-old males of two rat strains, Brown Norway (BN) and congenic BN.SHR-(Il6-Cd36)/Cub (BN.SHR4). These two inbred strains differ in a defined segment of chromosome 4, originally transferred from the spontaneously hypertensive rat (SHR) including the mutant Cd36 gene, a known target of DEX. Compared to BN, the standard-diet-fed BN.SHR4 showed higher cholesterol and triacylglycerol concentrations across many lipoprotein fractions, particularly in small VLDL and LDL particles. Total cholesterol was decreased by DEX by more than 21% in BN.SHR4 contrasting with the tendency to increase in BN (strain*DEX interaction p = 0.0017). Similar pattern was observed for triacylglycerol concentrations in LDL. The LDL particle size was significantly reduced by DEX in both strains. Also, while control BN and BN.SHR4 displayed comparable glycaemic profiles during oral glucose tolerance test, we observed a markedly blunted DEX induction of glucose intolerance in BN.SHR4 compared to BN. In summary, we report a pharmacogenetic interaction between limited genomic segment with mutated Cd36 gene and dexamethasone-induced glucose intolerance and triacylglycerol and cholesterol redistribution into lipoprotein fractions.
Keywords: Lipoproteins; dexamethason; Pharmacogenetics; Male; mutace; chromozomy; lipoproteiny; potkani inbrední SHR; Cholesterol; Dexamethasone; mužské pohlaví; triglyceridy; CD36 Antigens; krysa rodu Rattus; cholesterol; Animals; omezení příjmu potravy; Chromosomes; farmakogenetika; zvířata; Fasting; Rats; porucha glukózové tolerance; antigeny CD36; Rats, Inbred SHR; Mutation; Glucose Intolerance; Triglycerides